Vascular biology of uterine fibroids: connecting fibroids and vascular disorders. Issue 2 (8th July 2021) - Kirschen, Gregory W; AlAshqar, Abdelrahman; Miyashita-Ishiwata, Mariko; Reschke, Lauren; El Sabeh, Malak; Borahay, Mostafa A
Abstract : Fibroids are benign tumors caused by the proliferation of myometrial smooth muscle cells in the uterus that can lead to symptoms such as abdominal pain, constipation, urinary retention, and infertility. While traditionally thought of as a disease process intrinsic to the uterus, accumulating evidence suggests that fibroid growth may be linked with the systemic vasculature system, although cell-intrinsic factors are certainly of principal importance in their inception. Fibroids are associated with essential hypertension and preeclampsia, as well as atherosclerosis, for reasons that are becoming increasingly elucidated. Factors such as the renin–angiotensin–aldosterone system, estrogen, and endothelial dysfunction all likely play a role in fibroid pathogenesis. In this review, we lay out a framework for reconceptualizing fibroids as a systemic vascular disorder, and discuss how pharmaceutical agents and other interventions targeting the vasculature may aid in the novel treatment of fibroids.